The iInfluence of rapid maxillary expansion on craniocervical angulations one year after treatment - McGuinness, Niall John Patrick (The University of Edinburgh, 2005)
Introduction: Rapid maxillary expansion (RME) has been shown to increase nasal permeability and reduce nasal airway resistance. Numerous studies have examined the relationship between rapid maxillary expansion and the change in airway resistance, or have looked at the relationship between airway resistance and natural head position (NHP). Few studies, to date, have examined the relationship between RME and the change in NHP resulting from the consequent change in nasal airflow and decreased nasal resistance.

Hypothesis tested: The null hypothesis is that rapid maxillary expansion has no significant effect on airway patency which in turn influences craniocervical angulations.

Nature of study: prospective, longitudinal, non-randomised study of 43 consecutive adolescent patients who presented with uni- or bilateral crossbites in the permanent dentition, and who required rapid maxillary expansion as part of their overall orthodontic treatment

Methods: Cephalograms in natural head position were taken before, immediately after, and one year after RME and the craniofacial angulations obtained were compared with an historical control group from an earlier study.

Results: No significant changes in the craniofacial angles were found immediately after expansion. One year post-expansion, however, NSL/VER had reduced by 3.14°, (p<0.01), indicating a drop in head position, while OPT/HOR reduced by 2.13° (p<0.05), and CVT/HOR had reduced by 2.55° (p<0.05), indicating a more forward inclination of the cervical spine.

Conclusions: The results of this study suggest that when the nasal airway resistance decreases as a result of RME, changes in craniocervical angulations do take place, but this takes some time to occur. The decrease in head elevation relative to the true vertical is consistent with previous studies where increased nasal airflow has occurred. The forward inclination of the cervical spine, which, while statistically significant, may not be clinically significant, suggests that a possible small increase in airway resistance at the lower levels of the airway results from the increased nasal airflow. In order to accommodate this, the cervical spine inclines forward to increase the cross-sectional area of the lower airway and thereby achieving a possible equalisation of the total airway resistance between the nasal and the pharyngeal components.

The null hypothesis (that rapid maxillary expansion has no effect on craniocervical angulations in the long term) is not supported in this study.